Confederates in the Tropics : Charles Swett's Travelogue - Strom, Sharon Hartman (Book collections on Project MUSE., 2011)
Charles Swett (1828-1910) was a prosperous Vicksburg merchant and small plantation owner who was reluctantly drawn into secession but then rallied behind the Confederate cause, serving with distinction in the Confederate Army. After the war some of Swe.